Environmental Communication through Corporate Social Responsibility in Overcoming Peatland Fire Problems - Yasir (Universitas Pendidikan Ganesha, 2023)
Corporate communications should be integrated with environmental conservation campaigns. This research aims to explore the role of Pertamina's CSR in overcoming environmental problems related to peatland fires in Bukit Batu District, Bengkalis Regency. The researcher used a qualitative method with a case study approach. The subjects of this research are Pertamina's CSR practitioners and the community. The results show that Pertamina's CSR contributes in campaigning for environmental sustainability and preventing forest fires through the program of